UNEXPECTED RECORDS OF HERPETOFAUNA IN A PERI-URBAN PATCH OF THE CITY OF IQUITOS - RIOS-ALVA, Ehiko (2022)
The herpetofauna diversity of the Peruvian Amazon has considerable potential for conservation, research, and ecotourism. The lack of knowledge about amphibian and reptile species in peri-urban areas motivated us for this research in the Fernando Alcántara Bocanegra Research Center - CIFAB, in Iquitos, Peru, we conducted short and sporadic transect and pitfall trap sampling between June and September 2021 in small patches of white sand forest. We report the presence of four rare species of herpetozoa, three amphibians, and one ophidian: Pristimantis padiali, Ranitomeya amazonica, Synapturanus sp. "nanay" and Micrurus filiformis. These records are important because of their rarity in the herpetological collections of the country, particularly Synapturanus sp. "nanay" because of its fossorial habits and representing a species not yet described, and M. filiformis represents the second record for Iquitos after 45 years. The diversity of rare species in the periurban patch of CIFAB demonstrates that despite its location and the anthropogenic pressure on the environment, this type of patch in the Amazon is of vital importance for the preservation of these species.